STROKE KRIPTOGENIK - Al Rasyid (NEURONA, 2009)
INTRODUCTION CRYPTOGENIC STROKE DEFINE AS ISCHEMIC STROKE WITH UNCLEAR ETIOLOGIES EVENT FULL EXAMINATION HAD BEEN DONE THIS ENTITY APPROXIMATELY CONSISTED OF 40 OF ALL ISCHEMIC STROKE INCIDENCES A FEW NEWEST TECHNOLOGIES SHOWED THAT THE ETIOLOGY OF CRYPTOGENIC STROKE CAN BE EXPLAINED THOSE ARE INCLUDE HEMATOLOGY DISORDER SUCH AS HYPERCOAGULATION STATE DUE TO DISTURBANCES IN C PROTEIN LEVEL FREE S PROTEIN LEVEL LUPUS ANTICOAGULANT OR ANTIPOSPHOLIPID SYNDROME